1980
DOI: 10.1007/bf01851217
|View full text |Cite
|
Sign up to set email alerts
|

Are bloodflow changes after selective proximal vagotomy responsible for a necrosis in the gastric wall?

Abstract: Animal experiments were performed to investigate bloodflow distribution before and after selective vagotomy to explain gastric mucosa necrosis found in some patients after vogtomy. Flow measurements were made using the microsphere technique. Changes in the microcirculation were determined under basal and stimulated conditions (250 mg 2-desoxy-D-glucose). After selective vagotomy a reduction in bloodflow of up to 50% could be observed in all layers of the stomach. There were no differences in the bloodflow alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Surgical procedures on the stomach itself or lower esophagus may also provoke gastric necrosis. The pathogenesis of ischemic necrosis of the small curvature after proximal gastric vagotomy is explained by the relative blood deficiency characteristic of this region, associated with the reduction in mucous blood flow consequent to the vagotomy (15,16,21) . Concomitant splenectomy may further aggravate this risk due to the additional blood deprivation it causes (1,10,20) due to ligation of the short vessels and occasionally the left gastric omental artery or the posterior gastric artery when present.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures on the stomach itself or lower esophagus may also provoke gastric necrosis. The pathogenesis of ischemic necrosis of the small curvature after proximal gastric vagotomy is explained by the relative blood deficiency characteristic of this region, associated with the reduction in mucous blood flow consequent to the vagotomy (15,16,21) . Concomitant splenectomy may further aggravate this risk due to the additional blood deprivation it causes (1,10,20) due to ligation of the short vessels and occasionally the left gastric omental artery or the posterior gastric artery when present.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study are consistent with the findings in other studies. Investigations in animals using K 85 and 99m Tc clearance techniques, and the microsphere technique have demonstrated flow reductions in the stomach amounting to 50% after truncal vagotomy and PGV [3,15,16]. Intraoperative measurements with LDF before and after PGV have shown similar results along the devascularized part of the lesser curvature [17].…”
Section: Discussionmentioning
confidence: 95%
“…The effect of partial devascularization of the stomach on the gastric blood flow has been investigated during experimental conditions in animals [3,4]. Laser Doppler flowmetry (LDF) is a method which has been proven capable of reflecting changes in the gastric blood flow in animals, and in a previous study we have shown that it is a practical means of studying gastric circulation endoscopically in conscious man [5][6][7].…”
mentioning
confidence: 99%
“…Auch im Tierexperiment konnte durch SPV eine 50~oige Flowminderung nachgewiesen werden; allerdings erzielte hier vagale Stimulation eine generelle Flowsteigerung [22], so da6 die -Klinikern seit langem bekannte -hervorragende Collateralisierung der Magenwandgef'~iBe im Regelfall den Ausfall der A. gastrica sinistra zu kompensieren vermag. Die MWN nach SP V setzt somit eine Collateralgefgiflinsuffizienz voraus [22], was auch den Ergebnissen des ,,klinischen Massenversuchs SPV" entspricht.…”
Section: Pathogeneseunclassified